2010
DOI: 10.1021/jp106536m
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of C2−C8 n-Alkanes in Zeolites

Abstract: Adsorption of n-alkanes has been studied in the industrially relevant zeolites H-FAU, H-BEA, H-MOR, and H-ZSM-5 combining QM−Pot(MP2//B3LYP) with statistical thermodynamics calculations and assuming a mobile adsorbate. In H-ZSM-5, adsorption at the intersection site with the hydrocarbon chain extending in the straight channel (SC+I) as well as in the zigzag channel (ZC+I) has been studied. In addition, differential heats of adsorption and adsorption isotherms at temperatures from 301 to 400 K of all C3−C6 n-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
329
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(359 citation statements)
references
References 57 publications
29
329
1
Order By: Relevance
“…Just as an example, in the work of Eder et al [29] and De Moor et al [53], adsorption was carried out at p  10 -3 mbar (9.87·10 -7 atm) of (propane to n-hexane) and T  400 K. In an analogous way in the work of Dunne et al [54], Ramachandran et al [28] and Ferreira et al [55], among others, adsorption was always performed at p  9.87·10 -5 atm and T  423 K. From the work presented here, it is clear that by working under those experimental conditions it should be very difficult to unequivocally conclude about the homogeneity or heterogeneity of the surface for adsorption sites. Then, one should either follow the methodology presented here or to perform adsorption measurements under the appropriate range of pressures and temperatures to ascertain the homo or heterogeneity of the zeolite surface for catalytic cracking.…”
Section: Differential Heat Of Adsorption (H Ads )mentioning
confidence: 99%
“…Just as an example, in the work of Eder et al [29] and De Moor et al [53], adsorption was carried out at p  10 -3 mbar (9.87·10 -7 atm) of (propane to n-hexane) and T  400 K. In an analogous way in the work of Dunne et al [54], Ramachandran et al [28] and Ferreira et al [55], among others, adsorption was always performed at p  9.87·10 -5 atm and T  423 K. From the work presented here, it is clear that by working under those experimental conditions it should be very difficult to unequivocally conclude about the homogeneity or heterogeneity of the surface for adsorption sites. Then, one should either follow the methodology presented here or to perform adsorption measurements under the appropriate range of pressures and temperatures to ascertain the homo or heterogeneity of the zeolite surface for catalytic cracking.…”
Section: Differential Heat Of Adsorption (H Ads )mentioning
confidence: 99%
“…Eqs. (3) and (4)) are not very different from each other (see Table 6); however, the latter equation was employed since it has often been used for fitting volatile organic compounds adsorption on zeolites [29]. The fitted saturation capacity of MOR (see Table 6) is higher for toluene than for MTBE.…”
Section: Batch Experimentsmentioning
confidence: 99%
“…Entropies of activation are negative and have values between 40.6 (ethane) and 47.6 (n-butane/1) cal K -1 mol -1 for the proton exchange reaction in ZSM-5. From the Arrhenius equation, the entropy term contributes to the prefactor [35] and, thus, it slows down the proton exchange rate. Apparent Gibbs energies of activation at 500 K are in the range of 30.3 (ethane) to 40.6 (i-butane/3) kcal/mol.…”
Section: Apparent Reaction Barriersmentioning
confidence: 99%
“…De Moor et al[35] using QM-Pot(MP2//B3LYP) have shown that adsorption enthalpies of n-alkanes (C2-C8) in H-FAU, H-BEA,…”
mentioning
confidence: 99%